2019
DOI: 10.1177/1558944719837674
|View full text |Cite
|
Sign up to set email alerts
|

Median Neuropathy After Blood Draw Mimics Painful Clenched Fist Syndrome in a Child

Abstract: Background: Clenched fist syndrome is a rare disorder, often attributed to a conversion disorder without anatomic basis. Here, we review the literature surrounding clenched fist syndrome and challenge the assumption it is always psychiatric in origin, via description of a case of clenched fist syndrome responsive to surgical nerve decompression. Methods: An unusual case of clenched fist syndrome is reviewed and discussed. Results: A child presenting with clenched fist syndrome failed conservative measures cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The same situation exists for multiple of the other chronic nerve injury conditions treated in our patient population. Similar arguments to those above have been made elsewhere for complex regional pain syndrome, 16,37 painful neuroma, 17,18,21,62 chronic migraine headaches responsive to peripheral nerve blocks, 19,20,[63][64][65][66] and phantom limb pain. 67,68 The basis of any effective treatment is to target the cause.…”
Section: Significance Of Findingssupporting
confidence: 75%
See 1 more Smart Citation
“…The same situation exists for multiple of the other chronic nerve injury conditions treated in our patient population. Similar arguments to those above have been made elsewhere for complex regional pain syndrome, 16,37 painful neuroma, 17,18,21,62 chronic migraine headaches responsive to peripheral nerve blocks, 19,20,[63][64][65][66] and phantom limb pain. 67,68 The basis of any effective treatment is to target the cause.…”
Section: Significance Of Findingssupporting
confidence: 75%
“…In a sampling of 55,686 patients, they found that average health care charges were 3-fold higher for NP patients than matched control subjects ($17,355 vs $5715, respectively in year 2000). 35 Although Berger et al 35 examined medically managed patients, both causalgia 16,37 and PDN 38,39 have been repeatedly shown to be amenable to surgical intervention, and patients with both of these conditions were included in our study population, providing some degree of overlap to allow for drawing comparisons.…”
Section: Direct Costsmentioning
confidence: 99%
“…Although in most cases these symptoms resolve over time, they may require intervention or evolve into CRPS. [29][30][31] Nerve injuries from vascular access may be prevented with Plastic and Reconstructive Surgery • April 2023 648e increased awareness of anatomical distribution of nerves and with improved recognition and reporting of these injuries. 32 Furthermore, chronic pain and disability may be avoided after nerve injury with prompt referral and management.…”
Section: Discussionmentioning
confidence: 99%